Human Bodily Movement and Spirituality - Ivan Platovnjak; Vinko Zovko (Nova Prisutnost, 2023)
Movement is a reality that is linked to all dimensions of human life and action. People move in different ways and for different purposes. Various studies confirm that regular physical activity has a positive effect on a person’s overall health. In this article, the authors examine the connection between a person’s bodily movement and his or her spirituality. In four chapters, they reinforce the thesis that human beings move not only physically but also spiritually, and that their bodily movement enables them to live a more integrated spiritual life. In the first chapter, they briefly introduce movement as a fundamental reality of human life. In the second chapter they define spirituality, which should always be alive and also embodied in movement. In the third chapter, they describe Christian spirituality lived out in various forms of human bodily movement, limiting themselves to three basic ones: Walking, running, and dancing. As there is often a lack of connection between theory and practise, the last chapter briefly shows how to draw attention to bodily movement such that it has a greater influence on spiritual life.